2022-RA-1097-ESGO Acute torsion of the enlarged fibroid uterus in a postmenopausal woman. (20th October 2022) - Qadir, Dhilshad; Nadarajah, Ravichandran
Abstract : Introduction/Background: We present the case of a 76-year-old woman who presented with vague lower abdominal pain, diarrhea and vomiting. She was hypotensive and tachycardic at the Emergency Department. This rapidly improved upon intravenous fluid hydration and left lateral tilt. She had a distended abdomen with a 24-week sized uterus. Ultrasound pelvis showed multiple enlarged fibroids. She developed worsening intestinal obstruction. Methodology: A computed tomography (CT) scan showed multiple enlarged fibroids, showing a whorled appearance via a stalk. This suggested a torsion either of a large pedunculated fibroid or possible torsion of the uterus. The descending colon was compressed by this mass and there was mild dilatation of the small bowel, with hemorrhagic contents in the pelvis. She underwent surgery: Intra-operatively, blood stained ascites was found, and the uterus was enlarged with multiple fibroids. The uterus was torted 3 times at the isthmus and both fallopian tubes and ovaries appeared hyperemic. The patient underwent a total abdominal hysterectomy and bilateral salpingo-oophoorectomy. Histology showed hemorrhage in the myometrium and extensive hemorrhagic infarction of the fallopian tubes and ovaries, in keeping with uterine torsion. There was no malignancy. Results: Uterine torsion is defined as a rotation of greater than 45 degrees along the longitudinal axis of the uterus. This is uncommon in the gravid uterus, and is an even rarer occurrence in the elderly population. An enlarged fibroid uterus is a risk factor. Torsion of the uterus is a difficult diagnosis to make based on ultrasound alone, and CT imaging as well as laparotomy helped clinched the diagnosis. A high index of suspicion is required. Conclusion: Uterine torsion is rarely reported in the literature. It is difficult to diagnose but is an important consideration as unrecognised torsion and delay of surgical treatment may lead to serious complications such as hemorrhage, coagulopathy and sepsis.